Efficacy and Safety of Exercise Rehabilitation for Heart Failure Patients With Cardiac Resynchronization Therapy: A Systematic Review and Meta-Analysis - Ye, Li-fang; Wang, Shao-mei; Wang, Li-hong (Frontiers in Physiology, 2020)
Background: Many heart failure (HF) patients admitted to cardiac rehabilitation (CR) centers have a cardiac resynchronization therapy (CRT) device. However, information about the efficacy and safety of exercise rehabilitation in HF patients with a CRT device is scant. We assessed the effects of exercise rehabilitation in HF patients with a CRT device. Methods and Results: The PubMed, EMBASE, Cochrane Central Register of Controlled Trials, CINAHL, PsycInfo, China Biology Medicine, Wanfang, and China National Knowledge Infrastructure databases were searched comprehensively to identify randomized controlled trials (RCTs) published between January 1, 1990 and July 1, 2019 on exercise rehabilitation in HF patients with CRT devices. We identified seven studies published from 2006 to 2019, including 661 patients with an intervention duration of 8 to 24 weeks. Three studies reported all-cause mortality and serious adverse events, and no significant difference was found between exercise rehabilitation patients and controls at the longest available follow‐up (both P＞0.05; both I2=0%). Exercise rehabilitation patients exhibited a higher exercise capacity (peak oxygen uptake: random-effect WMD=2.02 ml/kg/min, 95% CI 0.62 to 3.41, P=0.005, I2=67.4%; exercise duration: fixed-effect WMD=102.34s, 95% CI 67.06 to 137.62, P<0.001, I2=25%) after intervention, despite the significant heterogeneity of studies. Left ventricular ejection fraction (LVEF) was significantly improved in exercise rehabilitation patients compared to that in controls (fixed-effect WMD=3.89%, 95% CI 1.50 to 6.28; P=0.001; I2=48.0%). Due to differences in health-related quality of life (HRQOL) assessment methods, we only pooled data that reported Minnesota Living with Heart Failure Questionnaire scores. Exercise rehabilitation patients exhibited a better HRQOL than controls (fixed-effect WMD=-5.34, 95% CI -10.12 to -0.56; P=0.028; I2=0%). Conclusions: Exercise rehabilitation may restore exercise capacity and cardiac function in HF patients with a CRT device. Furthermore, exercise training was associated with better HRQOL on follow-up.